Institutional innovation for accountability: The National Anti-Corruption System in Mexic - Alejandro Monsivais-Carrillo (Íconos)
The adoption of comprehensive institutional reforms that will establish the basis for improving the rule of law and accountability is needed to combat corruption. Nonetheless, this article posits that for these reforms to be effective the rigorous and sustained support of decisive actors is needed. Otherwise, no matter how progressive or innovative these reforms may seem on paper, institutional innovations could become ineffectual or cancelled de facto. This article advances this argument by providing an analysis of México’s National Anti-Corruption System (SNA). The SNA represents the case of an institutional innovation aimed at rebuilding accountability in a country characterized by persistent and pervasive political corruption. The analysis shows that SNA emerged from a legislative process that included the effective intervention of a network of experts and specialized organizations in this subject during a politically favorable moment due to corruption scandals that affected the incumbent government. As a result, the original initiative proposed by the government was replaced by a much more ambitious and progressive institutional framework. The analysis also shows that the SNA has been confronted with different challenges at a national and local level. Specifically, the ambivalent and weak commitment towards this system, highlighted by key actors in decisive moments, has limited its full implementation.